2020
DOI: 10.1016/j.isci.2020.100955
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Group Transfer Catalysis by Copper Complex with Redox-Active Ligand in an Entatic State

Abstract: Metalloenzymes use earth-abundant non-noble metals to perform high-fidelity transformations in the biological world. To ensure chemical efficiency, metalloenzymes have acquired evolutionary reactivity-enhancing tools. Among these, the entatic state model states that a strongly distorted geometry induced by ligands around a metal center gives rise to an energized structure called entatic state, strongly improving the reactivity. However, the original definition refers both to the transfer of electrons or chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Among these tools, the entatic state model relies on the fact that a strong steric distortion induced by ligands in the coordination sphere around a metal center produces an energized and highly reactive structure. Our recently published study revealed, that use of a highly-strained redox-active ligand facilitates a transfer of nitrogen-and carbon-containig group by copper complex 22 in as fast as two minutes, and therefore, it exhibits a strong increase in reactivity when compared to its unstrained analogue [40]. This example of a bioinspired small-molecule synthetic system combines two reactivity-enhancing features from metalloenzymes: entasis and redox cofactors.…”
Section: C-n Bond Formationmentioning
confidence: 96%
“…Among these tools, the entatic state model relies on the fact that a strong steric distortion induced by ligands in the coordination sphere around a metal center produces an energized and highly reactive structure. Our recently published study revealed, that use of a highly-strained redox-active ligand facilitates a transfer of nitrogen-and carbon-containig group by copper complex 22 in as fast as two minutes, and therefore, it exhibits a strong increase in reactivity when compared to its unstrained analogue [40]. This example of a bioinspired small-molecule synthetic system combines two reactivity-enhancing features from metalloenzymes: entasis and redox cofactors.…”
Section: C-n Bond Formationmentioning
confidence: 96%
“…Although the formation of a catalytically competent carbene radical is often accomplished by SET from the metal to the carbene, the group of Desage-El Murr employed the use of a redox-active ligand in combination with a copper metal center ( Scheme 8 ). 53 Copper has already been used to great effect in contemporary carbene transfer catalysis but generally has been observed to operate via two-electron concerted mechanisms. 54 Through use of two redox-active o -aminophenolate moieties bridged by a chiral binaphthyl group, the Desage-El Murr group has shown that their Cu-catalyzed cyclopropanation of styrenes likely operates via a stepwise radical mechanism.…”
Section: Catalysismentioning
confidence: 99%
“…24 Recently, an optically active bis(aminophenol) based on commercially available 1,1′-binaphthyl-2,2′-diamine has been prepared and complexed to copper. 25 Here we report the preparation of an optically active version of the EganH 4 ligand, (R,R)-BdanH 4 , using commercially available (R,R)-2,3-butanediol as starting material. Both this ligand and the bis(aminophenol) derived from (R)-1,1′-binaphthyl-2,2′-diamine, (R)-BiniqH 4 , are metalated stereoselectively to give group 10 bis(iminoxolene) complexes as single stereoisomers.…”
Section: Introductionmentioning
confidence: 99%
“…24 Recently, an optically active bis(aminophenol) based on commercially available 1,1′-binaphthyl-2,2′-diamine has been prepared and complexed to copper. 25…”
Section: Introductionmentioning
confidence: 99%